Influence of leguminous trees on soil nitrogen and phosphorus status of the sal forests - Hossain, Mohammad Zabed; Sultana, Tania; Ahmed, Ashfaque; Hoque, Sirajul (Dhaka University Journal of Biological Sciences, 2013)
Abstract not available Dhaka Univ. J. Biol. Sci. 22(2): 179-182, 2013 (July)